The lncRNA ANRIL is down-regulated in peripheral blood of patients with periodontitis - Gholami, Leila; Ghafouri-Fard, Soudeh; Mirzajani, Sara; Arsang-Jang, Shahram; Taheri, Mohammad; Dehbani, Zahra; Dehghani, Safoora; Houshmand, Behzad; Amid, Reza; Sayad, Arezou; Shams, Bahareh (Non-coding RNA research, 2020)
Long non-coding RNAs (lncRNAs) have crucial roles in lncRNAs in periodontal development and disorders of this tissue. A number of lncRNAs especially those regulating immune responses contribute in the pathophysiology of periodontitis. In the current case-control study, we assessed expression levels of two immune response-related lncRNAs namely the antisense non-coding RNA in the INK4 locus (ANRIL) and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in gingival tissues and blood samples of patients with periodontitis and healthy subjects. Expression of ANRIL was significantly lower in peripheral blood of patients compared with controls (Posterior Beta RE = -1.734, P value = 0.035). However, when diving study participants based on their gender, no significant difference was found between patients and sex-matched controls. Expression of this lncRNA was not different between periodontitis tissues and normal tissues. Expression of MALAT1 was not different between samples obtained from cases and controls. Tissue or blood expressions of ANRIL or MALAT1 were not correlated with age of either patients or controls. There were significant correlations between expression levels of ANRIL and MALAT1 in gingival tissues both in cases (r = 0.62, P < 0.0001) and in controls (r = 0.37, P < 0.0001). However, blood levels of these lncRNAs were not correlated with each other either in cases or in controls. Most notably, there was no significant correlation between expression levels of these lncRNAs in gingival tissues and in the blood of study participants. The current study indicates dysregulation of ANRIL in the peripheral blood of patients with periodontitis in spite of its normal levels in gingival tissues which might reflect disturbance in systemic immune responses in these patients. •Expression of ANRIL was significantly lower in peripheral blood of patients with periodontitis compared with controls.•Expression of ANRIL was not different between periodontitis tissues and normal tissues.•Expression of MALAT1 was not different between samples obtained from cases and controls.•Tissue or blood expressions of ANRIL or MALAT1 were not correlated with age.